Structural and Mutational Analysis of Functional Differentiation between Synaptotagmins-1 and -7 - Xue, Mingshan; Craig, Timothy K.; Shin, Ok-Ho; Li, Liyi; Brautigam, Chad A.; Tomchick, Diana R.; Südhof, Thomas C.; Rosenmund, Christian; Rizo, Josep (PLOS ONE, 2010)
Synaptotagmins are known to mediate diverse forms of Ca2+-triggered exocytosis through their C2 domains, but the principles underlying functional differentiation among them are unclear. Synaptotagmin-1 functions as a Ca2+ sensor in neurotransmitter release at central nervous system synapses, but synaptotagmin-7 does not, and yet both isoforms act as Ca2+ sensors in chromaffin cells. To shed light into this apparent paradox, we have performed rescue experiments in neurons from synaptotagmin-1 knockout mice using a chimera that contains the synaptotagmin-1 sequence with its C2B domain replaced by the synaptotagmin-7 C2B domain (Syt1/7). Rescue was not achieved either with the WT Syt1/7 chimera or with nine mutants where residues that are distinct in synaptotagmin-7 were restored to those present in synaptotagmin-1. To investigate whether these results arise because of unique conformational features of the synaptotagmin-7 C2B domain, we determined its crystal structure at 1.44 Å resolution. The synaptotagmin-7 C2B domain structure is very similar to that of the synaptotagmin-1 C2B domain and contains three Ca2+-binding sites. Two of the Ca2+-binding sites of the synaptotagmin-7 C2B domain are also present in the synaptotagmin-1 C2B domain and have analogous ligands to those determined for the latter by NMR spectroscopy, suggesting that a discrepancy observed in a crystal structure of the synaptotagmin-1 C2B domain arose from crystal contacts. Overall, our results suggest that functional differentiation in synaptotagmins arises in part from subtle sequence changes that yield dramatic functional differences.